A basic and clinical study on nasopharyngeal carcinoma in China - HUANG, Xiao-ming; CHEN, Jie-zhu; CHENG, Lei; PENG, Jie-ren; MIYOSHI, Akira (OTOLOGIA FUKUOKA, 1998)
Nasopharyngeal carcinoma (NPC) is one of the most common malignant tumors in China. It has its highest incidence rate in south China whose central region is Guangdong (Canton) Province where Cantonese is spoken. The perpose of this paper is mainly to describe the present status of NPC in China considering the following two main factors; 1. Epidemiologic character: Obvious geographic accumulation, susceptility of the population, an aggregation in certain families and a stabilization of the incidence rate were observed. 2. Etiology: The Epstein-Barr virus (EBV) is suspected to play an important role in the occurance of NPC. However, whether EBV is the only causative factor of NPC should be studied further. EBV may have a synergistic relationship with environmental pathogenic factors. Genetic susceptivity was closely related to NPC. Searching and isolating the oncogene and tumor suppressor gene is one of the most important molecular pathogenic mechanisms of NPC. Such genes reacting to NPC in China have been reported to be ras, c-myc, c-erB-2 and RB, p53, p16, etc. In addition, the expression of the TX gene has also been studied. 3. Early diagnosis: From 1986 to 1995, a longitudinal survey was completed on a cohort consisting of about 100, 000 subjects in the high risk area for NPC in Guangdong Province. A high risk population optimum screening program for NPC was proposed, and the criteria for both high risk populations and precancerous lesions of NPC were established and thus helped to detect NPC at earlier stage and thus individuals are found at a precancerous status. 4. Clinical stage: Compared with UICC (draft, 1996), the NPC new stage, proposed in 1992 in China, seems to be a more reasonable TN classification since it not only considers such factor as the aggressive degree of NPC but also is able to predict the prognosis and guide the therapy better. These twostaging systems are correlated to some extent to each other. 5. Therapy: The primary treatment for NPC is radiotherapy. Great progress has been made in different fractional therapy and individual therapeutic schemes. Three-dimentional conformal radiotherapy is a new treatment modality which improves the therapeutic technique of radiotherapy for NPC. In addition, it also helps to improve the survival rate and the quality of life (QOL) in patients undergoing chemotherapy as well as surgical operations at different stages of NPC. Recently, blocking precancerous lesions by drug and gene therapy is considered to be the key of research for NPC, and some progress has already been made in the field in China.